Internetowe materiały uzupełniające w nauczaniu języka niemieckiego – kryteria wyboru i oceny - Iwan, Piotr (Neofilolog, 2019)
The article aims to present the issue of evaluating selected supplementary materials with reference to traditional coursebooks for German available on the Internet. The analysis concentrates on publishers’ websites that offer an array of coursebooks and didactic aids such as dictionaries or spell-checkers. Additionally, we propose to make use of on-line texts and various sorts of authentic materials that have not been tailored for teaching purposes. We also provide criteria for systematic evaluation of educational computer programs and multimedia materials based on the analysis of information available on www.bundeskanzlerin.de, www.goethe.de, www.hueber.de. We conclude by constructing a catalogue of criteria that will be implemented in evaluating the applicability and quality of Internet materials for teaching German as a foreign language.